2018
DOI: 10.1103/physrevb.98.134513
|View full text |Cite
|
Sign up to set email alerts
|

Preformed pairs in flat Bloch bands

Abstract: In a flat Bloch band the kinetic energy is quenched and single particles cannot propagate since they are localized due to destructive interference. Whether this remains true in the presence of interactions is a challenging question because a flat dispersion usually leads to highly correlated ground states. Here we compute numerically the ground state energy of lattice models with completely flat band structure in a ring geometry in the presence of an attractive Hubbard interaction. We find that the energy as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 90 publications
9
89
0
Order By: Relevance
“…We also expect similar phenomena in other flat-band models, such as the saw-tooth, diamond and Lieb lattice models, which are to be realized in experiments [70][71][72][73][74], and also some studies in the Creutz ladder in the clean limit [75,76] pointed out the presence of conserved quantities. Such conjecture may support our results.…”
Section: Resultssupporting
confidence: 77%
“…We also expect similar phenomena in other flat-band models, such as the saw-tooth, diamond and Lieb lattice models, which are to be realized in experiments [70][71][72][73][74], and also some studies in the Creutz ladder in the clean limit [75,76] pointed out the presence of conserved quantities. Such conjecture may support our results.…”
Section: Resultssupporting
confidence: 77%
“…Note. Upon completion of this manuscript, a preprint appeared which tackled a similar problem [45], also finding formation of pair superfluidity away from half-filling. In addition to obtaining similar results, here we also quantitatively connect the results in the strongly interacting regime to a repulsive hardcore boson model which is superfluid for any finite interactions.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…While there is a long history for the study of flat-band systems as initiated by interests in ferromagnetism [1][2][3][4][5] , there is a recent surge of interests in flat-band superconductivity, where possibilities are explored for unconventional superconductivity favored by the flat-band structure [6][7][8][9] . As for attractive electron-electron interactions, Törmä's group has shown that a flat band can indeed favor superconductivity when the band is topological, with the superfluid weight lower-bounded by the topological number [10][11][12][13][14] . For repulsive interactions, on the other hand, a key question is how the presence of flat bands affects electron correlation processes.…”
Section: Introductionmentioning
confidence: 99%